Diving into online ratings to determine hotels' improvement priorities. (14th June 2019) - Zisos, Ioannis; Grigoroudis, Evangelos; Matsatsinis, Nikolaos; Spyridakos, Athanasios
Online ratings and reviews are currently considered as extremely effective tools for tourism professionals. Current research reveals that they affect, like no advertisement does, guests' vacation decisions. In this paper we build on existing large scale-survey on customers' ratings to explore the determinants of tourists' satisfaction in different hotel categories. The application of the MUSA method to online reviews has resulted in valuable conclusions regarding the quality of provided services, the identification of factors that influence customers' satisfaction, and the prioritisation of improvement that can improve customers' satisfaction levels. Data are taken from the popular hotel booking website Hotels.com and the case study examines available hotels in Chania, Greece. The final recommendations have been mainly based on the estimated global and partial value functions, the criteria weights, and the average satisfaction, demanding, and improvement indices, as provided by the MUSA method.